What Promotes Transfer of Staff Training Related to Challenging Behavior Displayed by Adults With Intellectual Disabilities?. Issue 2 (21st September 2021) - Martin, Aisling; Tyrrell, Sophie; Honey, Emma; Rodgers, Jacqui; Ingham, Barry
Abstract: Evidence is limited on the positive impact of staff training in challenging behavior of service users with ID; and the link between staff training and service user outcomes remains unclear. This review identified studies that investigate challenging behavior training for staff working with adults with ID within residential care settings to explore factors promoting transfer of training into practice. A mixed‐method review was adopted, and a systematic search identified 19 papers meeting the criteria for inclusion. The implicit themes involved in the transfer of training into practice were extracted from the literature and discussed in relation to: setting conditions; cognitive and emotional aspects; and organizational systems. As a first step toward moving forward with research in this relatively neglected area, key constructs were identified and a preliminary model of the transfer process proposed. Limitations of the review model were considered, and recommendations for future research discussed.